عالقة الصحة النفسية بأنجاز رفعة ) البنج بريس المستوي ( برياضة رفع االثقال البارالمبية لذوي االعاقة البدنية لفئة الشباب - Haider Ali Salman Abdul (Mustansiriyah Journal of Sports Science, 2024)
The development taking place in all areas of life, especially the sports side, and that the prevailing work at the present time is the higher levels and how to develop and raise the level of sports in order to achieve and achieve the records that achieve the required goals, as the psychological problems that face athletes in general and in terms of training and achievements competitions And that the responsibility rests with the workers in the sports side, that mental health is one of the important concepts in all sports, and one of these sports is weightlifting for people with disabilities, and weightlifting for people with disabilities is one of the competitive sports activities in which the psychological factor intervenes mainly in training and achievement Sports competitions by virtue of the specificity of theevent, the problem of the research through the follow-up of the researcher, being one of the workers with this segment, he deliberately asked a question to know the results, which is the relationship of mental health to achievement. Psychological and achievement of weightlifters for people with disabilities, and the researcher used the descriptive method and humiliation Because the descriptive approach is the approach that is suitable for obtaining the desired results from this problem, and the research sample was 8 quadrants. As for the fourth chapter, the researcher worked on analyzing, presenting and discussing the results. In the fifth chapter, the following follows: Mental health has a direct correlation with the skill of increasing strength for people with disabilities. As for the recommendations, the researcher recommends the need to pay attention to the development of mental health among lifters